Function of Proline Residues of MotA in Torque Generation by the Flagellar Motor of Escherichia coli - Braun, Timothy F. (American Society for Microbiology, 1999)
Bacterial flagellar motors obtain energy for rotation from the membrane gradient of protons or, in some species, sodium ions. The molecular mechanism of flagellar rotation is not understood. MotA and MotB are integral membrane proteins that function in proton conduction and are believed to form the stator of the motor. Previous mutational studies identified two conserved proline residues in MotA (Pro 173 and Pro 222 in the protein from Escherichia coli) and a conserved aspartic acid residue in MotB (Asp 32) that are important for function. Asp 32 of MotB probably forms part of the proton path through the motor. To learn more about the roles of the conserved proline residues of MotA, we examined motor function in Pro 173 and Pro 222 mutants, making measurements of torque at high load, speed at low and intermediate loads, and solvent-isotope effects (D(2)O versus H(2)O). Proton conduction by wild-type and mutant MotA-MotB channels was also assayed, by a growth defect that occurs upon overexpression. Several different mutations of Pro 173 reduced the torque of the motor under high load, and a few prevented motor rotation but still allowed proton flow through the MotA-MotB channels. These and other properties of the mutants suggest that Pro 173 has a pivotal role in coupling proton flow to motor rotation and is positioned in the channel near Asp 32 of MotB. Replacements of Pro 222 abolished function in all assays and were strongly dominant. Certain Pro 222 mutant proteins prevented swimming almost completely when expressed at moderate levels in wild-type cells. This dominance might be caused by rotor-stator jamming, because it was weaker when FliG carried a mutation believed to increase rotor-stator clearance. We propose a mechanism for torque generation, in which specific functions are suggested for the proline residues of MotA and Asp32 of MotB.